Implementasi Program Ismubaristik dalam Penguatan Pendidikan Ibadah di SMP Muhammadiyah 1 Medan - Dalimunthe, Sabina Rasmita; Sinaga, Ali Imran (Jayapangus Press, 2025)
This study aims to describe the implementation of the Ismubaristik program in strengthening worship education at SMP Muhammadiyah 1 Medan. The research focuses on the execution of program activities, supporting elements, and the challenges encountered during its implementation. A qualitative approach with a phenomenological method was adopted to explore students’ lived experiences while participating in the program. Data were collected through participatory observation, in-depth interviews with students and teachers, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the Ismubaristik program is carried out through various worship habituation activities such as Qur’an memorization (tahfidz), congregational prayer, funeral bathing practice, and hajj and umrah simulations. The program is systematically implemented through well-planned stages and regular evaluations. Its implementation has proven effective in fostering students’ religious character, as reflected in increased discipline, responsibility, and spiritual awareness in both school and daily life settings.